2019
DOI: 10.1002/jsfa.10004
|View full text |Cite
|
Sign up to set email alerts
|

The use of nanotechnology to increase quality and yield of fruit crops

Abstract: Nanotechnology is currently being widely employed in agriculture and horticulture. The most widely investigated and developed factor related to fruit trees is nanofertilizers (NFs), which play very important roles in increasing vegetative growth, improving reproductive growth and flowering, thereby increasing productivity, product quality and ultimately increasing shelf-life and decreasing fruit waste. These nanomaterials, which are generally sprayed at low concentrations on trees at different time intervals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(56 citation statements)
references
References 51 publications
0
56
0
Order By: Relevance
“…Recently, nanotechnology has found its way into agricultural systems. Application of minerals as nanoparticles in different shapes and sizes has high potential in increasing performance 4 and modulating environmental stress 5 . Although the positive effects of SiO 2 -NPs and Se-NPs spraying on agricultural crops has been well established, the combinational effect of Se/SiO 2 -NPs has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, nanotechnology has found its way into agricultural systems. Application of minerals as nanoparticles in different shapes and sizes has high potential in increasing performance 4 and modulating environmental stress 5 . Although the positive effects of SiO 2 -NPs and Se-NPs spraying on agricultural crops has been well established, the combinational effect of Se/SiO 2 -NPs has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of yield under drought stress could be due to many reasons including decrease of photosynthesis efficiency, leaf area, assimilate production, and decrease of water and mineral absorption by the root which ultimately decrease developmental and vegetative growth 2 . Exogenous application of Si and Se modulated the unfavorable effects of environmental stresses on the yield of different species 4 . Research has shown that Se played a critical role in different plants, ultimately affecting plant yield, factors such as starch accumulation in chloroplast, resistance enhancement to oxidative stress, delaying of senescence, and water status adjustment under stress conditions and increase of antioxidative capacity 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the progression of nanotechnology, the number of nanoparticles (NPs) used in consuming products has increased dramatically [1]. Nanotechnology is regarded as a 21st-century science, which has applications in many fields, i.e., biology, chemistry, and agriculture [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…With the progression of nanotechnology, the number of nanoparticles (NPs) used in consuming products has increased dramatically [1]. Nanotechnology is regarded as a 21st-century science, which has applications in many fields, i.e., biology, chemistry, and agriculture [1,2]. Metal NPs are widely used in commercial applications ranging from coating, topical sunscreens, soaps, antimicrobial agents and in agricultural applications [3].…”
Section: Introductionmentioning
confidence: 99%